Revision of the family Samaridae (Pleuronectiformes: Actinopterygii). - Alfonso, Noel Robert. (University of Ottawa (Canada), 2001)
The family Samaridae has 28 nominal species or subspecies, 22 of which are recognized in this study. Four new species (Samariscus sp., Samaris sp., Samaris sp. 1 and S. sp. 2) are described, two species names resurrected (S. cacatuae and S. onatus) and two species (S. filipectoralis and S. sunieri) and one subspecies (Samaris cristatus erythraeus) are synonymized. An artificial key was constructed for all species. The family is shown to be monophyletic, as are the three genera comprising the family; Plagiopsetta being the most plesiomorphic. Samaris and Samariscus are sister groups. Numerous apomorphies corroborate the monophyly of the S. cristatus complex (Samaris cristatus, S. cacatuae, S. ornatus and S. sp). In Samariscus, S. nielseni, S. corallinus and S. triocellatus form a monophyletic group. The family is restricted to the Indo-West Pacific. Species numbers are highest in the Indo-Malaysian region, drop off with increasing distance and are not found in the extreme eastern Pacific due to the eastern Pacific barrier.
Keywords: Biology, Zoology.